2005
DOI: 10.1097/01.fjc.0000161400.06704.1e
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Relaxes Human Internal Mammary Artery In Vitro

Abstract: Preliminary clinical studies of testosterone therapy in male patients with coronary artery disease raised promising results. However, there is no study on in vitro effects of testosterone in human isolated arteries. We investigated the effect of testosterone on contractile tone of human isolated internal mammary artery. The responses in human internal mammary artery (IMA) were recorded isometrically by a force-displacement transducer in isolated organ baths. Testosterone (10 nM to 100 microM) was added cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 36 publications
4
52
2
2
Order By: Relevance
“…[106][107][108] The involvement of potassium channels in testosterone-induced vasodilatation has also been studied by many researchers. [109][110][111] Cairrao et al 112 reported that an AR antagonist, flutamide, and an adenosine triphosphate-sensitive potassium-channel inhibitor, glibenclamide, had no influence on the testosterone relaxant effect, whereas a voltage-sensitive potassium-channel inhibitor, 4-aminopyridine, decreased this effect of testosterone. Opening of voltage-sensitive potassium channels induces hyperpolarization of the plasma membrane, which in turn may lead to the closing of L-type Ca2+ channels.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%
“…[106][107][108] The involvement of potassium channels in testosterone-induced vasodilatation has also been studied by many researchers. [109][110][111] Cairrao et al 112 reported that an AR antagonist, flutamide, and an adenosine triphosphate-sensitive potassium-channel inhibitor, glibenclamide, had no influence on the testosterone relaxant effect, whereas a voltage-sensitive potassium-channel inhibitor, 4-aminopyridine, decreased this effect of testosterone. Opening of voltage-sensitive potassium channels induces hyperpolarization of the plasma membrane, which in turn may lead to the closing of L-type Ca2+ channels.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%
“…Similarly, radial artery isolated from patients undergoing bypass surgery was shown to vasodilate in response to testosterone after pre-contraction with potassium chloride or phenylephrine (Seyrek et al 2007). The same group had previously found that testosterone relaxes isolated human internal mammary artery pre-contracted with potassium chloride or prostaglandins (Yildiz et al 2005).…”
Section: Figurementioning
confidence: 99%
“…sponse to testosterone may occur in via large-conductance Ca 2+ -activated K + channelopening action [112]. Clinical studies of testosterone therapy in male patients with coronary artery disease raised promising results.…”
Section: Artery Bypass 262mentioning
confidence: 91%
“…Testosterone may exert vasorelaxant effects on several vascular tissues [112][113][114][115][116][117][118][119]. We have studied effects of testosterone in the human IMA and found that vasorelaxant re-…”
Section: Testosteronementioning
confidence: 99%